Modeling and simulation of artificial hair cell sensor for underwater applications - Nawi, Mohd Norzaidi Mat; Manaf, Asrulnizam Abd; Arshad, Mohd Rizal (Akademi Sains Malaysia, 2013)
This article uses finite volume and finite element methods for optimization of the artificial hair cell sensor. The performance of the sensor was investigated for different materials such as sicon and polysilicon and by varying hair cell dimensions including width and length. The silicon material which has low young modulus was proposed based on the simulation performance. The performance of the hair cell sensor was achieved by increasing the hair cell length while increasing the width did not significantly influence the performance. The performance of the sensor was studied for its viscous force, deflection, von mises stress and sensitivity. From the simulation, the hair cell with a length of 1600 μm and 80 μm width was suggested for the subsequent analysis. Another way to improve the performance was by modifying the hair cell geometry and it was proved that the modified hair cell was more sensitive, based on the deflection. The angle of flow that hit the hair cell also affected the deflection of the sensor where the zero angle flow which was parallel to the substrate was the most effective angle. The limitations of the performance of hair cell for various fluid velocity were also discussed in this paper.